Muerte súbita - Donner, Richard; Emmett, Randall; Lerner, Avi.; Morse, David, 1953-; Mos Def (Cantante de rap); Rifkin, Arnold; Thompson, John.; Van Wyck, Jim.; Wenk, Richard; Willis, Bruce, 1955-; Alcon Entertainment (Firma); Cheyenne Enterprises; et al. (Burbank, CA : Warner Home Video, 2006)
Jack Mosley is a burnt-out detective who is assigned the unenviable task of transporting a fast-talking convict from jail, 16 blocks to the 100 Centre Street courthouse. However, as the two head off, Mosley learns that the man is supposed to testify against Mosley's colleagues, and the entire NYPD want the witness dead. Mosley must choose between loyalty to his colleagues and protecting the witness.
DISPONIBLE
Special features: Alternate ending (branched or stand-alone); deleted scenes with discussions by Richard Donner and writer Richard Wank.
Título del envase.
Director of photography, Glen MacPherson ; editor, Steve Mirkovich ; music, Klaus Badelt ; costume designer, Vicki Graef ; production designer, Arvinder Grewal ; visual effects supervisor, Evan Jacobs ; special effects supervisor, Marcus Rait.
Bruce Willis, Mos Def, David Morse.
MPAA rating: PG-13; for violence, intense sequences of action, and some strong language.
Keywords: New York (Estados Unidos). -- Departamento de Policía; Conducta criminal -- New York (Estados Unidos); Corrupción policial -- New York (Estados Unidos); Detectives -- New York (Estados Unidos); Drama; Películas cinematográficas; Testigos -- New York (Estados Unidos)